The Influence of Company Size, Working Capital, and Capital Structure on Profitability of Consumer Goods Companies Listed on the Indonesia Stock Exchange - Rizky Syah Fitri Lubis; Feby Milanie; Suwarno (Budapest International Research and Critics University, 2022)
This research was conducted to determine how the effect of firm size, working capital turnover, and debt to equity ratio on return on assets in consumer goods manufacturing companies listed on the Indonesia Stock Exchange. Data taken from www.idx.co.id. The data used was from 2012 to 2020. The research was conducted in 2022. The population in this research was 56 companies with 33 companies used as samples. This research used quantitative data that is processed with the Eviews 9 application with the panel regression method. The test results concluded that the variable company size and debt to equity ratio partially had a significant effect on return on assets, while working capital turnover partially did not have a significant effect on return on assets. Simultaneously, firm size, working capital turnover, and debt to equity ratio also had a significant effect on the return on assets of manufacturing companies in the consumer goods sector. The contribution given by the variables of firm size, working capital turnover, and debt to equity ratio to return on assets was 87.07%, while the level of closeness of the variables of firm size, working capital turnover, and debt to equity ratio to return on assets was very close or very strong.